A Unified Framework for High-Speed, Secure SDN: A Data Plane Approach - Tabatabaei Manesh, Seyyed Reza; Manavi Nezhad, Abbas (Management Strategies and Engineering Sciences, 2025)
The paper presents a scalable, software-centric architecture for secure, high-performance networking in the SDN environment. Our approach merges robust security with near line-rate throughput by integrating high-speed packet processing capabilities with optimized cryptographic operations into one cohesive SDN framework. At the heart of the architecture is the Data Plane Development Kit, which, through user-space processing, zero-copy buffering, advanced memory management, introduces low latency with reduced intruptions for packet handling. It integrates IPsec in such a way as to provide data confidentiality and integrity at the IP layer. The architecture takes advantage of vector packet processing to flexibly manipulate packets, adapt routing decisions on the fly, and make changes according to evolving network requirements. This forms one cohesive system that ties security with speed, giving operators agility to scale services, enforce policies, and protect sensitive data with software-driven efficiencies and minimal reliance on specialty hardware.